Occult and active hepatitis B virus detection in donated blood in São Paulo, Brazil. Issue 5 (9th March 2021) - Nishiya, Anna S.; Levi, José E.; de Almeida‐Neto, Cesar; Witkin, Steven S.; Ferreira, Suzete C.; Bassit, Leda; Sabino, Ester C.; Di‐Lorenzo‐Oliveira, Claudia; Salles, Nanci A.; Coutinho, Adenilson S.; Bellesa, Maria A.; Rocha, Vanderson; et al.
Abstract: Background: The present study determined the HBV antigen, antibody, and DNA status in blood donations deemed to be HBV positive. Individuals with an occult HBV infection (OBI), defined as being positive for HBV DNA but negative for HBV surface antigen (HBsAg), as well as those with active infection (HBsAg‐positive), were identified and characterized. Study Design and Methods: From a total pool if 198, 363 blood donations, we evaluated in a cross‐sectional study, 1106 samples that were positive in screening tests for antibody to HBV core antigen (HBcAb), HBsAg, and/or HBV DNA by nucleic acid testing (NAT‐HBV). The presence of genetic variants in the HBV pol/S gene in individuals with an active HBV infection was also determined. Results: OBIs were detected in six of 976 samples (0.6%) that were positive only for HBcAb. The rate of HBV active infection was 0.024% (48/198, 363) and there was a predominance of HBV sub‐genotype A1 (62.2%, 28/45), followed by D3 (17.8%, 8/45). Mutations in the S gene were found in 57.8% (26/45) and immune escape mutations in 37.8% (17/45) of active HBV‐infected donors. Among them, T123N, G145A, and D144G high‐impact immune escape mutations were identified. Conclusion: Highly sensitive molecular tests improve the capacity to detect OBIs. When NAT is performed in pooled samples, HBcAb test has value in the detection of donors with OBI and improves transfusion safety. Mutations in the S gene are frequent in HBsAg‐positive blood, including those associated with diagnostic failure and vaccine escape mutations.